Time in early childhood: Creative possibilities with different conceptions of time. (December 2016) - Farquhar, Sandy
Time is an important driver of pedagogy which is often overlooked in the busy atmosphere of an early childhood centre. Engaging philosophically with three different concepts of time, and drawing examples from literature and art to focus attention on how time is constituted in early childhood centres, this article argues that we inhabit the intersection of several different forms of time. Despite this, we tend to focus on only one form of time – chronological time, a formulation that is at the basis of our western education system. Our understandings of time impact on the way we think about education and the way we teach children. Incorporating different understandings of time in the space of early childhood has transformative potential, the enactment of which is at the heart of a good education. This article accepts the need for young children to be familiar with social conventions to do with time, but also advocates for an expanded subjectivity that flourishes within alternative notions of time.